Chitosan Nanoparticles for Enhanced Immune Response and Delivery of Multi-Epitope Helicobacter pylori Vaccines in a BALB/c Mouse Model - Rita Amaral; Tomás Concha; Jorge Vítor; António J. Almeida; Cecília Calado; Lídia M. Gonçalves (Pharmaceutics)
Background/Objectives: Helicobacter pylori is the leading cause of chronic gastritis, peptic ulcer, gastric adenocarcinoma, and mucosal-associated lymphoma. Due to the emerging problems with antibiotic treatment against H. pylori in clinical practice, H. pylori vaccination has gained more interest. Oral immunization is considered a promising approach for preventing initial colonization of this bacterium in the gastrointestinal tract, establishing a first line of defense at gastric mucosal surfaces. Chitosan nanoparticles can be exploited effectively for oral vaccine delivery due to their stability, simplicity of target accessibility, and beneficial mucoadhesive and immunogenic properties. Methods: In this study, new multi-epitope pDNA- and recombinant protein-based vaccines incorporating multiple H. pylori antigens were produced and encapsulated in chitosan nanoparticles for oral and intramuscular administration. The induced immune response was assessed through the levels of antigen-specific IgGs, secreted mucosal SIgA, and cytokines (IL-2, IL-10, and IFN-γ) in immunized BALB/C mice. Results: Intramuscular administration of both pDNA and recombinant protein-based vaccines efficiently stimulated the production of specific IgG2a and IgG1, which was supported by cytokines levels. Oral immunizations with either pDNA or recombinant protein vaccines revealed high SIgA levels, suggesting effective gastric mucosal immunization, contrasting with intramuscular immunizations, which did not induce SIgA. Conclusions: These findings indicate that both pDNA and recombinant protein vaccines encapsulated into chitosan nanoparticles are promising candidates for eradicating H. pylori and mitigating associated gastric diseases in humans.